Hydrolytic enzymes-producing ability of species of actinomycetes and bacteria associated with wilted banana plants (Musa sp.) - AULIA ARDHI; KARINA CUCHA AHMAD; HANITA NOVRIANTI; ERA YURISA HUSNA; MARDI YULIS; NOVA WAHYU PRATIWI; SARYONO SARYONO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Ardhi A, Ahmad KC, Novrianti H, Husna EY, Yulis M, Pratiwi NW, Saryono. 2019. Hydrolytic enzymes-producing ability of species of actinomycetes and bacteria associated with wilted banana plants (Musa sp.). Biodiversitas 20: 1147-1153. Banana plants contain many nutrients that enable microbes to grow and attack them, causing wilting disease. Microbes growing on the stumps and soil around banana plants are believed to have the ability to produce hydrolytic enzymes. The purpose of this study was to determine the ability of actinomycetes and bacteria isolated from the stumps and soil of wilted banana plants in producing hydrolytic enzymes, namely cellulase, inulinase, amylase, and protease. The confirmation tests of hydrolytic enzymes-producing ability were conducted by inoculating the microbes into media containing CMC, inulin, starch, and skim milk, using the method of paper disc diffusion. From the subculture results, there were 18 isolates of actinomycetes which have been identified as Nocardia, Actinobiospora, Nocardiopsis, Streptomyces, Streptoverticillium, Streptosporangium, and Microbiospora, as well as 40 bacterial isolates with 9 genera of bacteria, namely Xanthomonas, Erwinia, Pesudomonas, Proteus, Ralstonia, Escherichia, Staphylococcus, Caulobacter, and Neisseria, were found. As many as 8 actinomycetes and 40 bacterial isolates indicated the ability to degrade amylum, 39 bacterial and 18 actinomycetes isolates could degrade cellulose, 34 bacterial and 13 actinomycetes isolates could degrade inulin. The highest cellulase ratio was shown by Nocardia sp. LBKURCC101 (3.43) and Ralstonia sp. LBKURCC112 (3.90). The actinomycetes isolate of Nocardia sp. LBKURCC104 and bacteria Pseudomonas sp. LBKURCC133 gave the highest inulinase ratio of 3.36 and 3.47 respectively. In selective amylase media, the highest ratio of 3.10 and 3.80 was found in actinomycetes Nocardia sp. LBKURCC104 and bacteria Erwinia sp. LBKURCC125.